1997
DOI: 10.1016/s0277-9536(97)00054-3
|View full text |Cite
|
Sign up to set email alerts
|

Russian medical care in the 1990s: A user's perspective

Abstract: Abstract:This article examines medical utilization patterns and attitudes toward the medical care system among the citizens of Russia's second largest city, St. Petersburg. It focuses upon the extent to which both attitudes towards and usage of medical care institutions have changed in the immediate post-Soviet period. A particular concern has been to determine the degree to which utilization and perceptions vary across the socioeconomic status hierarchy. The data were collected in two stages: a mass survey (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
1
28
0
1
Order By: Relevance
“…Year of publication 1991-1998 7 English: [18,22,24,32,33,44] Russian: [19] [21]. The priorities of the reforms still appear depend on the Heads of the Ministry of Healthcare and corroborate a principle that was and still is put into practice -"new lords, new laws".…”
Section: Characteristics Of Publications Number Of Publications Refermentioning
confidence: 99%
See 3 more Smart Citations
“…Year of publication 1991-1998 7 English: [18,22,24,32,33,44] Russian: [19] [21]. The priorities of the reforms still appear depend on the Heads of the Ministry of Healthcare and corroborate a principle that was and still is put into practice -"new lords, new laws".…”
Section: Characteristics Of Publications Number Of Publications Refermentioning
confidence: 99%
“…Inter-regional variation in access could be related to regional variations in healthcare financing and stages of implementation of healthcare reforms among regions [16,43]. For example, there were variations of costs per service and ability-to-pay for services among regions upon comparison of prices, both formally and informally [22,44]. However, inter-regional inequalities could be also caused by geographical remoteness from the capital and the fact that a limited number of highly specialized hospitals are mainly located in the largest cities [45].…”
Section: Effects On Equitymentioning
confidence: 99%
See 2 more Smart Citations
“…One reason for this is that ambulances would sometimes double as freelance taxis to earn extra money, thereby causing delay in emergency response (4). One study looking at views about the healthcare system among the general population in St. Petersburg found that one of the most frequently mentioned worries was about the emergency care system and its ability to provide adequate care for patients with sudden and unexpected life-threatening illness or accidents (7). There is no formal training in either adult or pediatric emergency medicine throughout most of the Commonwealth of Independent States (CIS) (8 -10).…”
Section: Introductionmentioning
confidence: 99%